DEVELOPMENT OF CARDIOVASCULAR RISK FACTORS IN YOUNG PEOPLE (E Global Congress, 2024)
This article delves into the development of cardiovascular risk factors in young people, shedding light on the shifting landscape of cardiovascular diseases (CVDs) towards affecting younger populations. As sedentary lifestyles, poor dietary habits, and rising obesity rates become increasingly prevalent among the youth, the burden of CVD risk factors such as hypertension, dyslipidemia, and metabolic syndrome is on the rise. Moreover, the pervasive influence of tobacco and substance use, coupled with psychosocial stressors, further compounds the cardiovascular risk profile of young individuals. Early prevention strategies, including education, behavioral modification, and targeted interventions, are highlighted as essential components in mitigating the development and progression of CVD risk factors in young populations. By addressing these risk factors during formative years, public health initiatives can effectively curb the trajectory of CVDs and promote heart health across the lifespan.